2001
DOI: 10.1016/s0022-2860(01)00639-1
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy and ab initio MO study of the molecular structure and vibrational spectra of α- and γ-pyrones

Abstract: The molecular structures and vibrational spectra of the monomeric forms of a-and g-pyrones were investigated by ab initio MO calculations, undertaken at the HF/6-31G p level of theory, and vibrational spectroscopy, including matrix-isolation FTIR spectroscopy. A complete assignment of the vibrational spectra of the studied compounds isolated in an argon matrix, at 8 K, or in the condensed phases, at room temperature, is presented and the vibrational data correlated with some important structural parameters. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
4
10
0
2
Order By: Relevance
“…From the analysis of the two datasets (calculated vs experimental) it can be concluded that the calculated geometry for the monomer in vacuum is in excellent agreement with the X‐ray data, indicating that, in the condensed phase, the intermolecular interactions introduce only relatively unimportant effects on the electron distribution in the coumarin molecules. It is worth noticing that this result follows the trend previously observed for both α ‐ and γ ‐pyrone (45), where intermolecular interactions in the condensed phases were also found to affect the structure and vibrational properties of the molecules only very slightly.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…From the analysis of the two datasets (calculated vs experimental) it can be concluded that the calculated geometry for the monomer in vacuum is in excellent agreement with the X‐ray data, indicating that, in the condensed phase, the intermolecular interactions introduce only relatively unimportant effects on the electron distribution in the coumarin molecules. It is worth noticing that this result follows the trend previously observed for both α ‐ and γ ‐pyrone (45), where intermolecular interactions in the condensed phases were also found to affect the structure and vibrational properties of the molecules only very slightly.…”
Section: Resultssupporting
confidence: 88%
“…On the whole, the structural results clearly demonstrate that π ‐delocalization in the pyrone sub‐unit of coumarin is very limited, being even less important than in α ‐pyrone (45). An interesting way to evaluate the level of π ‐electron delocalization is the aromaticity index HOMA (Harmonic Oscillator Measure of Aromaticity), defined by Kruszewski and Krygowski (46–48): where n is the number of bonds considered, and α is an empirical constant (for C−C and C−N bonds α= 257.7 and 93.52, respectively) fixed to have HOMA = 0 for a model nonaromatic system, and HOMA = 1 for a system with all bonds equal to an optimal value R opt , which is assumed to be achieved for a fully aromatic system.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The structural and vibrational spectroscopy data for the ground state demonstrated that no extensive π-system electron delocalization occurs in the pyrone moiety. Comparison of the spectroscopic results obtained for the monomeric species with those obtained for the room temperature condensed phase reveal that intermolecular interactions in these phases do not affect the structure and vibrational properties of pyrone derivatives [16].…”
Section: -Introductionmentioning
confidence: 86%
“…4, является предсказательной. Располагаем только экспериментальными данными [14] для базового соединения -Г-П.…”
Section: научный отдел 14unclassified